GOOD GOVERNANCE DALAM SUDUT PANDANG ISLAM (PENJELASAN AL-QUR’AN) - Muhammad Sulton Arif; Mohamad Djasuli (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
Indonesia as a country with a majority Muslim population must know and understand the principles of Islamic GCG in running a business. The Qur'an explains how a government must be managed in order to realize good governance. In the Qur'an does not explicitly regulate the implementation of good governance in government. the concept of good governance in the Qur'an can not only be applied to government, but must be applied to any organization and in our daily lives. The Qur'an explains the concepts of responsibility, transparency, justice and equality. Creating good governance based on the principles that have been formulated, namely transparency, accountability, responsibility, independence and fairness. The purpose of the article is to find out Good Corporate Governance from an Islamic point of view in the Qur'an. Data collection techniques use literature studies through written sources such as online data searches/internet searching and literature studies.